Changes on the match profile of the South African Currie Cup tournament during 2007 and 2013 - Vahed, Y.; Kraak, W.; Venter, R. (International Journal of Sports Science & Coaching, 2016)
In rugby union, several law changes were implemented between 2007 and 2013, yet the impact of these law changes on the profile of the game has not been assessed to date. The aim of this study was to determine the effect of the law changes on the scoring, time interval, general skills and contact profiles of the South African Currie Cup during the 2007 (n=37) and 2013 (n=33) seasons. A total of 70 matches were analysed using video analysis software. The frequencies of 37 performance indicators were used to address the aim of the study. The scoring profile revealed that fewer tries were scored (p=0.07), while the number of penalty goals increased significantly (p<0.01). The time interval profile showed that stoppages decreased significantly (p<0.01). The skills profile revealed a significant increase in the number of passes (p<0.01) and a decrease in the number of handling errors, offloads and kicks (p<0.01). The contact profile revealed a significant increase in the number of rucks/mauls and tackles completed (p<0.01) and a decrease in scrums and line-outs (p<0.01). The study revealed that the South African game have move to a game that is more physical and continuous.